Recombinant vascular endothelial growth factor 121 decreases vascular cell adhesion molecule-1 in murine pre-eclampsia model placenta - Sulistyowati, Sri; Sondakh, John Arianto; Yuliantara, Eric Edwin; Respati, Supriyadi Hari; Soetrisno, Soetrisno (Universa Medicina, 2016)
BackgroundPreeclampsia is one of the major contributors to maternal and fetal morbidity and mortality. Imbalance of soluble Fms-like tyrosine kinase (sFlt-1) as anti-angiogenic factor and vascular endothelial growth factor (VEGF) as pro-angiogenic factor plays a role in the pathogenesis of preeclampsia. Endothelial dysfunction in preeclampsia causes vascular cell adhesion molecule-1 (VCAM-1) to be expressed on its surface. This study aims to evaluate the effect of recombinant VEGF-121 on VCAM-1 expression in the placenta of a murine preeclampsia model. Methods An experimental analytical study conducted from February until March 2016 in the Biomedical Laboratory, Faculty of Veterinary Medicine, Airlangga University. The study sample consisted of 30 pregnant mice, divided into three groups, i.e. 10 normal pregnant mice, 10 mice with preeclampsia model and 10 mice with preeclampsia model and recombinant VEGF-121 therapy. All animals were subjected to immunohistochemical examination of VCAM-1 expression in their placentas. The results were assessed semiquantitatively according to a modified Remmele method. Data analysis was done using one-way ANOVA and Tukeyâs multiple comparisons method. ResultsMean VCAM-1 expression in normal (0.97 Â± 0.54%) murine placentas, compared with placentas (2.94 Â± 0.96%) of murine preeclampsia models (p=0.000), while mean VCAM-1 expression in placentas of murine preeclampsia models with VEGF intervention was 2.14 Â± 0.68% (p=0.030).Conclusion Recombinant VEGF-121 can reduce VCAM-1 expression in placentas of murine preeclampsia models. The present study has shown the potential benefits of VEGF therapy, justifying serious consideration of this therapeutic approach for use in women with preeclampsia.